Voltage and Current Analysis of Oil Immersed Power Transformer due to Lightning Impulse with Different Insulation Conditions - Abdul Rahim, Nabil Asyraf; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Journal of Electronic Voltage and Application, 2022)
Insulation breakdown is a common cause of transformer failure. Insulation is used to prevent current from flowing between points in an electrical system with varying potentials. Lightning strikes are a natural cause of transient overvoltage in the power system. A lightning strike is an impulsive transient variation with a polarity that is unidirectional (positive or negative). This research aims to determine waveform of voltage and current with its peak and RMS value for oil immersed power transformer with lightning impulse. Specifically, it analyses the data obtained for a good and poor insulation of the transformer. A comprehensive lightning impulse test was conducted on the transformer. Both high voltage and low voltage winding was subjected to a test voltage ranging from 50% to 75% integrity of the entire test voltage. Following that, three consecutive full-wave lightning impulses at 100% of the test voltage are applied. The result showed a significant disparity value for both conditions especially for current peak and RMS value which are 215.8 A and 156.7 A respectively due to shorten tail time which obtained from poor insulation is 20.1 ?s. This results in a significant rise in the current value, as the tail time is supposed to be between 40 ?s and 60 ?s. Although the difference between voltage peak and RMS value is minuscule which are 2.4 kV and 1.7 kV respectively, the voltage waveform for poor insulation is unstable. As a result, a lightning impulse will affect a huge number of apparatuses or electrical equipment when it strikes a transformer with an insulation fault. Preventive maintenance is necessary for the safe and reliable operation of transformers. Maintenance identifies issues early and helps avert future deterioration.